Arg-Gly-Asp-D-Phe-Lys peptide-modified PEGylated dendrimer-entrapped gold nanoparticles for targeted computed tomography imaging of breast carcinoma. (July 2015) - Li, Kangan; Zhang, Zhuoli; Zheng, Linfeng; Liu, Hong; Wei, Wei; Li, Zhiyu; He, Zhiyan; Larson, Andrew C; Zhang, Guixiang
Aim: To investigate cyclo (Arg-Gly-Asp-D-Phe-Lys) peptide (RGD)-modified PEGylated dendrimer-entrapped gold nanoparticles (PEGylated Au DENPs-RGD) for targeted computed tomography (CT) imaging of breast carcinomas.Materials & methods: PEGylated Au DENPs-RGD were synthesized and characterized. Then, the PEGylated Au DENPs-RGD for targeted CT imaging were investigated using the MDA-MB-435 cell line, an integrin-rich breast carcinoma cells, and mice with MDA-MB-435 xenograft tumors. Finally, silver enhancement staining and integrin αv β3 immunohistochemistry of the tumors were performed.Results: The synthesized PEGylated Au DENPs-RGD were spherical, water dispersible and biocompatible nanoprobes with a gold nanoparticle core size of 2.8 nm. Due to the presence of the Au nanoparticles, the PEGylated Au DENPs-RGD displayed a higher x-ray attenuation intensity than Omnipaque at the same Au or I concentrations. The conjugated RGD ligand can specifically identify and target overexpressed integrin receptors on MDA-MB-435 cells. After intravenous injection, these nanoprobes accumulated in the targeted area of mice with MDA-MB-435 xenograft tumors, which enabled the tumor to be detected by CT imaging. The histological results confirmed the imaging results.Conclusion: The PEGylated Au DENPs-RGD can be used as targeted nanoprobes with good biocompatibility for targeted CT imaging and diagnosis of integrin-positive tumors.